Investigating the effect of optimal cytoreduction in the context of platinum sensitivity in high‐grade serous ovarian cancer. (2nd July 2022) - Cardillo, Nicholas; Devor, Eric; Calma, Christian; Pedra Nobre, Silvana; Gabrilovich, Sofia; Bender, David P.; Goodheart, Michael; Gonzalez‐Bosquet, Jesus
Abstract: Introduction: The survival benefits of surgical cytoreduction in ovarian cancer are well‐established. However, the surgical outcome has never been assessed while controlling for the efficacy of chemotherapy. This leaves the possibility that cytoreduction may not be beneficial for patients whose cancer does not respond well to adjuvant treatment. We sought to answer whether surgical cytoreduction independently improves overall survival when controlling for chemotherapy outcome. Material and Methods: We performed a retrospective case–control study using our institution's ovarian cancer database to evaluate the effect of optimal cytoreduction on advanced stage, high‐grade serous ovarian cancer. Patients' characteristics were compared using both univariate and multivariate regression modeling to assess for independent predictors of overall survival. Results: A total of 470 patients were assessed for inclusion; 234 responders to chemotherapy and 98 nonresponders. Significant survival characteristics were identified and included in the multivariate analysis. Independent predictors of survival in the multivariate analysis were age, responder status, optimal cytoreduction, neoadjuvant chemotherapy, and number of chemotherapy cycles. Kaplan–Meier survival curves showed improved survival for both patients who responded to chemotherapy and for those undergoing optimal cytoreduction ( p  < 0.001). We also demonstrated improved survival for patients receiving optimal cytoreduction among both nonresponders and responders ( p  < 0.001). Conclusions: Our analysis shows that patients who undergo optimal cytoreduction have an overall survival benefit regardless of their response to chemotherapy. Therefore, cytoreduction should be considered in all patients, even in those with advanced disease, if an optimal result can be achieved. This study was underpowered to assess patients who received neoadjuvant chemotherapy as a separate subgroup, but the order of treatment was controlled for in the overall analysis. Abstract : 332 patients with high grade serous tubo‐ovarian cancer were analyzed in a retrospective cohort study and separated into groups based on their response to chemotherapy. When controlling for whether they responded to platinum‐based chemotherapy, an optimal cytoreduction was found to be a significant predictor of improved overall survival.